The Hilālian in the areas of Banu Hammad Between Submission and Rebellion ) 405-547H/1014-1152ad) - messaoudi, Nour Eldine (The Algerian Historical Journal, 2026)
This research includes a study on the involvement of the Banū Hilāl tribes in the political projects of the Hammadid state. By enlisting them in the ranks of the Hammadi army, to benefit from their combat capabilities in order to be a support for them to achieve their expansionist projects to extend their influence over the lands of the Maghreb. We initially discussed the origins of the Hilāl tribes and their activity in the East before migrating to the Maghreb. We also talked about the relationship between the Emirates of Banū Zīrī and Banu Hamad during that period, and their expansionist disputes. Then, we discussed the invasion of the the Banū Hilāl in the central Maghreb after their victory in the battle of Sbeiba against the Hammadi, and how the princes of Banu Hammad worked to court the Hilali to join their ranks.